2016
DOI: 10.1080/19325037.2016.1203841
|View full text |Cite
|
Sign up to set email alerts
|

Recall and Believability of the Tips From Former Smokers Campaign Among University Students

Abstract: Background Tobacco media campaigns are effective, but less is known regarding the impact on college students. Purpose The purpose was to test the effects of an on-campus Tips television campaign on frequency and believability of ads recalled and to assess demographic and personal factors associated with believability. Methods A quasi-experimental pre-post design was used to assess the 8-week campaign with three Tips ads. Two randomly-selected cohorts of college students (N = 1,593) from a large public univ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…A prior study of randomly sampled students from this university yielded a similar sample demographic profile (70% female, 81% White/non-Hispanic, 72% lower undergraduate). 19 In addition, the response rate is relatively modest (13.9%). This concern is mitigated given a recent study of college student survey response rates 20 which found that estimates of outcome measures were generally reliable even with response rates as low as 5-10%, as long as at least 500 students were invited to participate (invited 2,671 invited in this study).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…A prior study of randomly sampled students from this university yielded a similar sample demographic profile (70% female, 81% White/non-Hispanic, 72% lower undergraduate). 19 In addition, the response rate is relatively modest (13.9%). This concern is mitigated given a recent study of college student survey response rates 20 which found that estimates of outcome measures were generally reliable even with response rates as low as 5-10%, as long as at least 500 students were invited to participate (invited 2,671 invited in this study).…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…This study was part of a larger study to evaluate the impact of an 8-week CDC Tips from Former Smokers television campaign conducted at a large public university in the Southeastern U.S. ( Ickes et al, 2016 ) Two cohorts of students were surveyed two months apart prior to and after the campaign. We combined the sample of current smokers from these two cohorts for this analysis.…”
Section: Methodsmentioning
confidence: 99%